العراقية Bos indicus والأبقار Camelus dromedariues دراسة نسجية مقارنة لكبد الإبل - قاسم سكر ضمياء; عبد علي الشمري هيفاء; جاسم الطه طه (University of Thi-Qar Journal of Science, 2010)
The camel liver is highly lubulation in comparative with liver cows , so this study show highly significant difference between the two species in the size of the hepatocytes and their nuclei . the hepatocytes & nucleus in camel liver is very polyhedrale and large than that in cow liver which ismore arrange .the diameter of sinusoid in cow liver is larger than that in camel